Mucosal Vaccination With Recombinant Tm-WAP49 Protein Induces Protective Humoral and Cellular Immunity Against Experimental Trichuriasis in AKR Mice - Wei, Junfei; Hegde, Venkatesh L.; Yanamandra, Ananta V.; O’Hara, Madison P.; Keegan, Brian; Jones, Kathryn M.; Strych, Ulrich; Bottazzi, Maria Elena; Zhan, Bin; Sastry, K. Jagannadha; Hotez, Peter J. (Frontiers in Immunology, 2022)
Trichuriasis is one of the most common neglected tropical diseases of the world’s poorest people. A recombinant vaccine comprised of Tm-WAP49, an immunodominant antigen secreted by adult Trichuris stichocytes into the mucosa of the cecum to which the parasite attaches, is under development. The prototype is being evaluated in a mouse model of Trichuris muris infection, with the ultimate goal to produce a mucosal vaccine through intranasal delivery. Intranasal immunization of mice with Tm-WAP49 formulated with the adjuvant OCH, a truncated analog of alpha-GalCer with adjuvanticity to stimulate natural killer T cells (NKT) and mucosal immunity, induced significantly high levels of IgG and its subclasses (IgG1 and IgG2a) in immunized mice. This also resulted in a significant reduction of worm burden after challenge with T. muris infective eggs. The addition of QS-21 adjuvant to this vaccine formulation further reduced worm counts. The improved protection from the dual-adjuvanted vaccine correlated with higher serum antibody responses (IgG, IgG1, IgG2a, IgA) as well as with the induction of antigen-specific IgA in the nasal mucosa. It was also associated with the robust cellular responses including functional subsets of CD4 T cells producing IL-4, and cytotoxic CD8 T cells expressing granzyme B. The worm reduction achieved by mucosal immunization was higher than that induced by subcutaneous immunization. Intranasal immunization also induced a significantly higher nasal mucosa-secreted antigen-specific IgA response, as well as higher functional cellular responses including CD4+IL4+ (Th1) and CD8+GnzB+ (Th2) T cells, and antigen-specific INFγ-producing T cells in both spleen and MLNs and antibody-producing B cells (CD19+B220+/B220+GL7+). Mucosal immunization further induced long-term T lymphocyte memory with increased central (CD62L+CD44+) and effector (CD62L-CD44+) memory subsets of both CD4 and CD8 T cells at 60 days after the last immunization. In summary, intranasal immunization with recombinant Tm-WAP49 protein-induced strong protection versus murine trichuriasis. It represents a promising vaccination approach against intestinal nematodes.